The Relationship Between Brand Quality and Brand Relationship: Delivering the Hotel Brand as Promised - Ezgi Erkmen (Journal of Tourismology, 2017)
The purpose of this study is to understand how the difference between advertised brand and experienced brand during employee-customer interaction affects relationship quality of hotel guests. A quantitative research was adopted by surveying hotels guests to understand the moderating role of the gap between promised brand and experienced brand. The results of study indicate that if the difference between promised and experienced brand is low, hotel guests are more likely to develop trust and continue their brand relation with the hotel. Therefore, hotels need to include their employees in branding in order to deliver a brand experience as it is promised.